The use of conventional and ultrasonic energy in dyeing of 100% wool woven fabrics - (:unkn) unknown (My University, 2010)
This paper focuses on the dyeing behaviour of wool woven fabrics produced from 100% wool sirospun and conventional woollen yarns. The ultrasonic energy was applied as a dyeing method and was compared with the conventional dyeing technique. Three wool woven fabrics made of 2/2 Z twill and having different weight of fabrics with different warp and weft densities were produced. Later, optimum dyeing conditions were studied by using two different temperatures and two different times on the ultrasonic energy method. The wool woven fabrics were dyed in both dyeing techniques by using a commercial Dorolan Black MSRL (acidic dye) and later these samples were tested for their colour measurement by a reflectance spectrophotometer. Both dyeing techniques were compared according to the data obtained. It was observed that ultrasonic energy technique was successfully adapted to wool dyeing process. 100% wool wollen fabrics were dyed with the ultrasonic probe at 90oC temperature with the reduce amount of time (64 minutes less than conventional dyeing) compare to conventional dyeing technique. The lighter sirospun wool fabrics (158.6 g) were also dyed easily with the use of ultrasonic energy in all conditions (in both temperatures: 80oC-90oC and in both times: 80min-90min).
Keywords: Colour measurement; Dyeing; Sirospun; Ultrasonic energy; Wool; Woollen yarn; Woven fabric